2014
DOI: 10.1007/s00127-014-0852-x
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic density is not associated with psychological distress in Turkish-Dutch, Moroccan-Dutch and Surinamese-Dutch ethnic minorities in the Netherlands

Abstract: These results suggest that individual demographic and socio-economic risk characteristics outweigh the influence of neighbourhood attributes on mental health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 26 publications
2
13
0
Order By: Relevance
“…Several studies in the US and UK found effects of own-group density on health, sometimes positive [9, 29, 30], but sometimes negative [3133]. However, similar to our results, Schrier et al [12] found no association between own-group density and psychological distress for Surinamese, Turks, and Moroccans in the four largest Dutch cities (including Amsterdam).…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Several studies in the US and UK found effects of own-group density on health, sometimes positive [9, 29, 30], but sometimes negative [3133]. However, similar to our results, Schrier et al [12] found no association between own-group density and psychological distress for Surinamese, Turks, and Moroccans in the four largest Dutch cities (including Amsterdam).…”
Section: Discussionsupporting
confidence: 85%
“…The association between ethnic composition of the residential environment and health presumably operates through social capital and exposure to discrimination [9]. However, evidence from the United States (US) and Europe is equivocal, in that the strength and direction (both negative and positive) of the association vary by ethnic minority group, spatial scale, and outcome measure [8–12]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, living in such neighborhoods with many co-ethnics can also lead to a high level of social support, which is a predictor of positive psychological adjustment ( Van de Vijver & Phalet, 2004). The notion that ethnic density functions as a buffer against perceived experiences of exclusion and prejudice in the Dutch society and protects from suffering a negative effect on their mental health is questioned by Schrier et al (2014). Their research shows that other risk factors, such as individual socioeconomic background, have more influence on mental health than neighborhood characteristics.…”
Section: Ethnic Densitymentioning
confidence: 99%
“…In the Dutch media, this minority adolescent group is often portrayed as having behavioural problems, including being quick to anger and responding aggressively. Consequently, Moroccan‐Dutch individuals report high levels of perceived discrimination (Schrier et al, ). Although studies show that parents and teachers report more externalizing problems among Moroccan‐Dutch than Dutch adolescents (Stevens et al, ), these differences do not appear in self‐reports.…”
Section: Introductionmentioning
confidence: 99%